Exclusive breastfeeding duration and determinants among Brazilian children under two years of age - WARKENTIN, Sarah (2013)
ObjectiveThe present study described the duration and identified the determinants of exclusive breastfeeding. MethodsThe study used data from the Pesquisa Nacional de Demografia e Saúde da Criança e da Mulher 2006 (National Demographic and Health Survey on Women and Children 2006). Data were collected using questionnaires administered by trained professionals and refer to a subsample of 1,704 children aged less than 24 months. The estimated durations of exclusive breastfeeding are presented according to socioeconomic, demographic and epidemiological variables. Kaplan Meier estimator curves were used to produce valid estimates of breastfeeding duration and the Cox’s proportional hazards model was fitted to identify risks. ResultsThe median estimated duration of exclusive breastfeeding was 60 days. The final Cox model consisted of mother’s age <20 years (hazard ratio=1.53, 95% confidence interval=1.11-1.48), use of pacifier (hazard ratio=1.53, 95% confidence interval=1.37-1.71), not residing in the country’s southeast region (hazard ratio=1.22, 95% confidence interval=1.07-1.40) and socioeconomic status (hazard ratio=1.28, 95% confidence interval=1.06-1.55). ConclusionThe Kaplan Meier estimator corrected the underestimated duration of breastfeeding in the country when calculated by the current status methodology. Despite the national efforts done in the last decades to promotebreastfeeding, the results indicate that the duration of exclusive breastfeeding is still half of that recommended for this dietary practice to promote health. Ways to revert this situation would be ongoing educational activities involving the educational and health systems, associated with advertising campaigns on television and radio mainly targeting young mothers with low education level and low income, identified as those at high risk of weaning their children early